The Influence of the Yanbu’a Method on the Quality of Quran Reading Among Students in the Tahfidz Subject at SMP Al-Maksum - Putri Nur; Widya Masitah (Dinasti Publisher, 2024)
This study aims to examine the effect of the Yanbu’a method on the reading quality of the Qur'an among students in the tahfidz subject in the eighth grade at Al-Maksum Junior High School. Using a quantitative approach with experimental methods, data was collected through observation, pretest-posttest tests, and documentation. The research results show that the average score of students during the pretest was 60.93%, which then significantly increased to 85.03% after the yanbu’a musyafahah program method was applied. The percentage of students who achieved a high learning outcome category with scores between 80-100 on the pretest was 0% out of 31 students. After the pretest, there was a significant increase, with 83.871% or 26 students reaching that category on the posttest following the implementation of the Yanbu’a musyafahah program. Inferential statistical analysis supports this finding, indicating a significant difference between the pretest and posttest results. In conclusion, the application of the Yanbu’a method is effective in improving the quality of Quran reading and the learning completion rate of students in the eighth grade at Al-Maksum Junior High School.